Robert Ludlum's The Bourne imperative [compact disc, unabridged] - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2012)
The man Jason Bourne fishes out of the frozen lake is near death, bleeding profusely from a gunshot wound and drowning. He awakens as an amnesiac, with no memory of who he is or why he was shot, and Bourne is eerily reminded of his own past.